2021
DOI: 10.4314/gjg.v13i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the causes, impact and solutions to global warming among undergraduate students from different schools in the University of The Gambia

Abstract: Climate Change is unequivocal and occurring at an alarming pace. Increasing greenhouse gas emissions, their concentration in the atmosphere and increased energy absorption have resulted in in changes in climate. This study was a cross sectional study conducted from April 12th to May 12th, 2021. The survey was conducted online using Google form that was circulated via "WhatsApp" groups and emails received from the University admissions office. This study comprises of students in their; first year 26.5%, second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This result was supported by [10] in Egypt who conducted a study entitled "Impact of awareness program regarding health consequences of climate change on knowledge, perception and daily life practices among nursing students" found that the mean age of nursing students was 20.2±1.58. While, this finding in disagreement with [11] in Gambia, who studied "Awareness of the causes, impact and solutions to global warming among undergraduate students from different schools in the university" found that only 46% of the respondents in the study were between the ages of 21 and 25.This may be due to the sample of students had enrolled in the fourth academic year at Faculty of Nursing. Related to sex, the current study showed that near three fifth of nursing students were females.…”
Section: Discussionmentioning
confidence: 68%
“…This result was supported by [10] in Egypt who conducted a study entitled "Impact of awareness program regarding health consequences of climate change on knowledge, perception and daily life practices among nursing students" found that the mean age of nursing students was 20.2±1.58. While, this finding in disagreement with [11] in Gambia, who studied "Awareness of the causes, impact and solutions to global warming among undergraduate students from different schools in the university" found that only 46% of the respondents in the study were between the ages of 21 and 25.This may be due to the sample of students had enrolled in the fourth academic year at Faculty of Nursing. Related to sex, the current study showed that near three fifth of nursing students were females.…”
Section: Discussionmentioning
confidence: 68%